A 2D fully coupled hydro-mechanical finite-discrete element model with real pore seepage for simulating the deformation and fracture of porous medium driven by fluid. (February 2018) - Yan, Chengzeng; Jiao, Yu-Yong
Highlights: A 2D fully coupled hydro-mechanical finite-discrete element model with real pore seepage is proposed. The model can simulate the deformation and fracture of rock with an arbitrary complex fracture network driven by fluid pressure. The proposed method can capture crack initiation and propagation, the interaction of hydraulic fractures and natural fractures, and the fluid pressure distribution in the rock mass. Abstract: Based on the finite-discrete element method (FDEM), a 2D fully coupled model with real pore seepage is proposed. This model can solve the problem of the deformation and fracture of porous medium driven by fluid. In this model, the fluid flow in the fracture is expressed by the cubic law, while the fluid flow in the rock matrix is characterized by Darcy's law and solved by the finite volume method. The interaction between pore seepage and fracture seepage is realized at the fracture. Three analytical solutions are presented to verify the correctness of the proposed model. The results show that the numerical solutions agree well with the analytical solutions. In addition, a hydraulic fracturing problem with a complex fracture network is studied using this model. The simulation results show that the model can capture the fracture initiation, propagation, and intersection, the interaction of natural fractures and newly generated fractures, and the evolution of fluid pressure during hydraulic fracturing. The model can be used not only to simulate hydraulic fracturing in shale gas and geothermal mining but also to solve a series of geomechanical problems related to the effect of fluid. Thus, this model has broad application prospects.